Postpartum-specific Vital Sign Reference Ranges. Issue 1 (March 2022) - Green, L.J.; Pullon, R.; Mackillop, L.H.; Gerry, S.; Birks, J.; Salvi, D.; Davidson, S.; Loerup, L.; Tarassenko, L.; Mossop, J.; Edwards, C.; Gauntlett, R.; et al.
Abstract : ( Obstet Gynecol . 2021;137:295–304. doi: 10.1097/AOG.0000000000004239) Though the majority of maternal deaths occur in the postpartum period (57% in the United States), compared with the antenatal and intrapartum periods, the postpartum period doesn't receive as much focus. Abnormal vital signs such as venous thromboembolism, hemorrhage, sepsis, and gestational hypertensive disorders are the leading cause of death during the postpartum period. Little data exists for postpartum vital signs. This study aims to estimate maternal postpartum vital sign ranges.